Pedal to the metal: velocity and power in high-level golfers - Parker, J.; Lundgren, L. E. (The Journal of Strength and Conditioning Research, 2021)
In most rotational power assessments, discrete variables are used for subsequent examination; however, movements are continuous, and data can be collected in time series. The purpose of this investigation was to examine the velocity- and power-time series characteristics of a standing rotation test and identify relationships with golf performance. Thirty-one golfers performed a golf-specific rotation test (GSRT) with 3 different resistances (6, 10, and 14 kg) in a robotic engine system. Time series of velocity and power was calculated from the raw data, and each repetition was then normalized to 0-100%. Principal component analyses (PCAs) were performed on velocity and power waveforms. The PCA used an eigenvalue analysis of the data covariance matrix. The relationship between clubhead speed (CHS) and all principal components (PC) was examined using linear regression. Ten velocity parameters and 6 power parameters explained 80% of the variance in the data. For velocity, the first 2 PCs identified both magnitude and phase shift features while PCs 3-5 identified difference features. For power, the first 2 PCs identified both magnitude and phase shift features, the third PC identified a phase shift feature, and the fourth PC identified a difference feature. The highest relationship with CHS was shown for GSRT with 14 kg in PC2 for power (R2 = 0.48, p < 0.001). The PCA of the GSRT power test could distinguish intraindividual differences, external loads, and sex-based differences. Athletes should focus on accelerating smoothly through the movement, particularly with heavier loads, and not pulling aggressively at the beginning of the rotational movement to achieve maximum power.